2017
DOI: 10.4269/ajtmh.17-0121
|View full text |Cite
|
Sign up to set email alerts
|

Dengue Virus Coinfection in Human Immunodeficiency Virus-1-Infected Patients on the West Coast of Mexico

Abstract: Dengue virus infection in human immunodeficiency virus (HIV)-positive patients is not well studied. Previous reports suggest a transitory inhibition of the HIV-1 viral load, as well as a benign clinical progression of dengue. The follow-up of six HIV-1-infected patients, diagnosed and hospitalized with dengue virus infection in the State of Colima, Mexico, was carried out to analyze the progression of this viral coinfection. The presence of dengue virus serotype 1 was confirmed through molecular tests. No seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…She was positive for NS antigen by ELISA and the diagnosis was consistent with the dengue hemorrhagic fever. In varicella, even though co-infections with bacterial complications, particularly skin superinfections, hand-foot-mouth disease, scrub typhus are reported, dengue co-infection was not reported in the literature (2,4,5,(9)(10)(11). Rebahi et al (5), reported purulent meningitis in a child with varicella.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…She was positive for NS antigen by ELISA and the diagnosis was consistent with the dengue hemorrhagic fever. In varicella, even though co-infections with bacterial complications, particularly skin superinfections, hand-foot-mouth disease, scrub typhus are reported, dengue co-infection was not reported in the literature (2,4,5,(9)(10)(11). Rebahi et al (5), reported purulent meningitis in a child with varicella.…”
Section: Discussionmentioning
confidence: 99%
“…Maitland reported three cases of meningococcal disease temporally associated with chickenpox (10). Francisco Espinoza-Gomez et al (11), reported six cases of HIV-1 patients associated co-infection with the dengue virus from Mexico. In our child it is unlikely that varicella and dengue co-infections to occur concomitantly unless the patient is immunocompromised.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is feasible to assume that it is highly probable to have co-infections/superinfections between HIV-1 and DENV in areas of the world where DENV is endemic. Indeed, cases of co-infections were reported [127][128][129][130][131]. From a dengue disease perspective, co-infection with HIV-1 mostly resulted in a mild disease [127,128,131], or when severe dengue was present, no deadly cases of Dengue hemorrhagic fever (DHF) or Dengue shock syndrome (DSS) were reported [130,132].…”
Section: Hiv-1 and Denguementioning
confidence: 99%